An equivalent linearization for the drag force in the Morison’s equation using Hermite polynomial error sample function - Thinh, N. H.; Anh, N. D.; Cuong, D. A. (Vietnam Journal of Mechanics, 1998)
Within the scope Gaussian equivalent linearization (GEL), a new mean square criterion based on Hermite polynomial error sample functions for determining the coefficients of the equivalent linearization is proposed to linearize non-linear functions of the zero mean Gaussian random process. Application to the Morison’s equation for wave forces is presented that shows significant improvements over the corresponding accuracy of the classical GEL.